ANALISIS PENGARUH FAKTOR INTERNAL DAN EKSTERNAL TERHADAP HARGA SAHAM (Studi Kasus pada Perusahaan Sektor Property dan Real Estate yang Terdaftar di BEI) - Bella Anindita Apsari (Universitas Negeri Medan, 2015)
The existence of capital market in Indonesia can be seen from the number of investors who invest their shares in property and real estate sectors. From the perspective of the macro economy, the property sector has a very broad scope of business so that the stimulation of business property in turn will affect the economic growth and work opportunities. Property also be an important indicator of economic health of a country. In this research, are considered internal factors that affect stock prices and the real estate property sector is to look at financial ratios such as the ratio of Return On Equity (ROE) dan Earning Per Share (EPS) while external factors were used in this study is variable exchange rate and BI Rate This study uses 8 company property and real estate sector with the best issuer ratings, with a study period of years 2010-2014 (annual period). The technique analysis panel regression. The results of this research is the Return On Equity (ROE) have a a significant negative effect on stock prices and the real estate property sector, Earning Per Share (EPS) have a a significant positive effect on stock prices and the real estate property sector, exchange rate have a not significant positive effect on stock prices and the real estate property sector, BI Rate have a a not significant negative effect on stock prices and the real estate property sector.